2012
DOI: 10.5194/acp-12-3687-2012
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ions at Alpine waterfalls

Abstract: Abstract. During a three-year field campaign of measuring waterfall generated ions, we monitored five different waterfalls in the Austrian Alps. Most measurements were performed at the Krimml waterfall (Salzburg, Austria), which is the biggest waterfall in Europe, and the Gartl waterfall (Mölltal, Austria). We characterized spatial, time and size distributions of waterfall-generated ions under the influence of surrounding topography. The smallest ions with boundary diameters of 0.9, 1.5 and 2 nm, were measured… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 39 publications
1
41
0
3
Order By: Relevance
“…In contrast to our observations during rainfall, their observations showed a continuous increase but no significant maxima at higher particle sizes. In another study near five different waterfalls in Austrian Alps, waterfall-generated ions were found to have peaks at 1.5-2.0 nm and 120 nm [Kolarz et al, 2012]. Moreover, concentrations of ions of < 0.6 nm were observed to increase with decrease in their size.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast to our observations during rainfall, their observations showed a continuous increase but no significant maxima at higher particle sizes. In another study near five different waterfalls in Austrian Alps, waterfall-generated ions were found to have peaks at 1.5-2.0 nm and 120 nm [Kolarz et al, 2012]. Moreover, concentrations of ions of < 0.6 nm were observed to increase with decrease in their size.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 95%
“…From the results of their measurements, they concluded that the bursts of intermediate ions produced during splashing of raindrops cannot be considered as the nucleation bursts. In a 3 year field campaign in Austrian Alps, Kolarz et al [2012] detected high negative ion concentration gradients with only moderate increase in positive ions in the vicinity of waterfalls. Blanchard [1955Blanchard [ , 1966, Gathman and Trent [1968], Gathman and Hoppel [1970], and Reiter [1994] have studied the formation of charged droplets resulting from the busting of bubbles on the water surface and sea spray.…”
Section: Introductionmentioning
confidence: 99%
“…The waterfall effect 26 Lenard (1892) reported that the air near the base of a waterfall was negatively charged; subsequent 27 laboratory experiments indicated that breakup of the water stream is required; a jet of water did not 28 lead to charge separation (Lenard, 1915). The phenomenon now known as Lenard,waterfall,29 balloelectric or spray electrification is well established, having been confirmed at various times and 30 places (Natanson,1950) (Pierce,1965) (Reiter, 1994) (Laakso, 2007) (Kolarz, 2012). Recent work has 31…”
mentioning
confidence: 91%
“…shown that the numbers of both negatively and positively charged small clusters of water molecules less 32 than 30 nm in diameter are increased but that the negatively charged 'air ions' are at least ten times 33 more numerous than the positive ones (Kolarz, 2012). spray.…”
mentioning
confidence: 99%
“…For example, special ionizers were tested that employ the stimulation of plants placed in a salt solution with high electric voltage [20], and their influence and effect on the tracheas of laboratory (sewer-) rats were evaluated, together with an analysis of the state of their blood. Measuring the concentration of air ions is widely applied in monitoring the degree of air pollution, hygiene checks at workplaces, health therapy -speleotherapy [21]- [23], in the study of electric phenomena in the atmosphere and, topically, in forecasting earthquakes [24], [25] or other weather anomalies. Aplin [26] describes the effects of atmospheric electricity on its surroundings and the manner it is generated in the troposphere.…”
Section: Introductionmentioning
confidence: 99%